Esclavitud, independencia y poder simbólico en las prácticas jurídicas. (Costa Rica 1816-1824) - González Valverde, Ana Lorena (2021)
This paper aims to uncover the underlying dominion relations between owners and slaves, concealed in certain notarial deeds of manumissions carried out in Costa Rica between 1816 and 1824. The purpose is to open a discussion on the role that the social practice of law has as a symbolic factor in the field of historical events, which settles and filters at the same time, the intentions of the social actors using it. It is argued that manumissions in Costa Rica did not occur only because of the generosity of male and female slave owners, but also because of the economic factors that lead them to manumit.